Comparative Genomics Provides Insights Into Genetic Diversity of Clostridium tyrobutyricum and Potential Implications for Late Blowing Defects in Cheese - Podrzaj, Lucija; Burtscher, Johanna; Domig, Konrad J. (Frontiers in Microbiology, 2022)
Clostridium tyrobutyricum has been recognized as the main cause of late blowing defects (LBD) in cheese leading to considerable economic losses for the dairy industry. Although differences in spoilage ability among strains of this species have been acknowledged, potential links to the genetic diversity and functional traits remain unknown. In the present study, we aimed to investigate and characterize genomic variation, pan-genomic diversity and key traits of C. tyrobutyricum by comparing the genomes of 28 strains. A comparative genomics analysis revealed an “open” pangenome comprising 9,748 genes and a core genome of 1,179 genes shared by all test strains. Among those core genes, the majority of genes is enriched in basic functionalities related to intracellular survival. A large part of the accessory genome is composed of sets of unique, strain-specific genes ranging from about 5 to more than 980 genes. Furthermore, functional analysis revealed several strain-specific genes related to secondary structure and defense mechanisms that might facilitate survival under stressful environmental conditions. Phylogenomic analysis divided strains into two clades: clade I contained human, mud and silage isolates, whereas clade II comprised cheese and milk isolates. Notably, these two groups of isolates showed differences in certain hypothetical proteins, transcriptional regulators and ABC transporters involved in resistance to oxidative stress. Interestingly, distant genetic relationship between one strain (Cl_52) and the other 28 strains indicates that Cl_52 may not belong to the species C. tyrobutyricum but rather represent a novel species within the genus Clostridium. To the best of our knowledge, this is the first study to provide comparative genomics of C. tyrobutyricum strains related to LBD. Importantly, the findings presented in this study highlight the broad genetic diversity of C. tyrobutyricum, which might help us understand the diversity in spoilage potential of C. tyrobutyricum in cheese and provide some clues for further exploring the gene modules responsible for the spoilage ability of this species.